The Relationship between ESG Scores and Corporate Governance Practices on Corporate Financial Stability in the Infrastructure Sector in Indonesia - Judijanto, Loso; Destiana, Rina (West Science Accounting and Finance, 2024)
This study examines the relationship between Environmental, Social, and Governance (ESG) scores and corporate governance practices on corporate financial stability in Indonesia's infrastructure sector. Using a quantitative approach, data were collected from 60 infrastructure companies through a Likert-scale questionnaire (1-5) and analyzed using SPSS version 25. The findings reveal that both ESG scores and corporate governance practices significantly and positively influence corporate financial stability, with governance practices showing a stronger impact. The results underscore the synergistic relationship between ESG and governance, highlighting their importance in mitigating risks and enhancing resilience in high-capital industries like infrastructure. These insights provide actionable recommendations for corporate leaders and policymakers to strengthen governance and sustainability practices, fostering long-term financial stability and competitiveness.